Phenomenological Attitude in Descriptive Phenomenological Psychological Research - Dragan, Tatjana; Sondaitė, Jolanta (Psichologija, 2023)
Phenomenological approach is one of the leading approaches in the practice of qualitative psychological research. Two perspectives can be distinguished in it: descriptive phenomenology and interpretive phenomenology. A researcher intending to apply a phenomenological strategy is expected to be able to practice the phenomenological attitude, which plays a key role both in the process of data collection and analysis. This article focuses on the field of descriptive phenomenology based on E. Husserl’s philosophy and represented by A. Giorgi and F. Wertz in the context of phenomenological psychology. The purpose of the article is to reveal the essential characteristics of the phenomenological attitude, to unfold theoretical emphases and to provide certain practical insights for those researchers who decided to conduct a descriptive phenomenological study. Literature analysis is used to achieve the goal. The phenomenological attitude is described using two contexts – E. Husserl’s phenomenological philosophy and the phenomenological psychology based on its assumptions – briefly presenting both, revealing their connections and distinguishing features.
Keywords: phenomenological attitude; phenomenological psychology; descriptive phenomenological research